Stereoselective Synthesis and Antimicrobial Studies of Allo-Gibberic Acid-Based 2,4-Diaminopyrimidine Chimeras - Dima Depp; Noémi Regina Sebők; András Szekeres; Zsolt Szakonyi (Pharmaceuticals, 2025)
Background: Gibberellins (GAs) are a family of tetracyclic ent-kaurenoid diterpenes found widely in several commonly used plants. Besides agricultural applications, gibberellins play an important role in the synthesis of bioactive compounds, especially those with antiproliferative and antibacterial activity. Methods: A series of gibberellic acid-based 2,4-diaminopyrimidines was designed and synthesized from commercially available gibberellic acid. The antimicrobial activity of the prepared compounds was also explored in B. subtilis, S. aureus, E. coli, and P. aeruginosa bacteria, as well as in C. krusei and C. albicans fungi. Results: The treatment of gibberellic acid with hydrochloric acid under reflux conditions resulted in aromatization followed by rearrangement to form allo-gibberic acid. The key intermediate azido alcohol was prepared according to the literature methods. The second key intermediate azidotriol was synthesized by the stereoselective dihydroxylation of the allylic function by the osmium (VIII)-tetroxide/NMO system. Starting from azide intermediates, click reactions were also carried out with 4-monoamino- and 2,4-diaminopyrimidines functionalized with the N-propargyl group. The new chimeric compounds, coupled with gibberellins thus obtained, were characterized by 1D- and 2D-NMR techniques and HRMS measurements. While the 4-monoamino-substituted derivatives exhibited only weak antibacterial activity, they demonstrated significant antifungal effectiveness against C. krusei. In general, 5-chloro-substituted pyrimidine derivatives displayed more consistent biological activities compared to their 5-fluoro counterparts, with the exception of one derivative, which showed acceptable activity against both C. krusei and C. albicans. The two derivatives featuring 5-chloro and 2-((4-(trifluoromethyl)phenyl)amino substituents proved to be highly effective against P. aeruginosa, making them promising candidates for further research. Aiming to elucidate the molecular interactions between the active compounds and their potential targets, molecular docking studies were conducted using AutoDock Vina 1.1.2. involving the most active compounds against P. aeruginosa.Conclusions: The biological effects of 2-monoamino or 2,4-diamino substitution as well as the effect of chloro or fluoro substitution at position 5 of the pyrimidine ring combined with the allo-gibberic acid moiety were determined. Compounds with selective antibacterial activity against P. aeruginosa as well as selective antifungal activity against C. krusei and C. albicans fungi were identified.